2020
DOI: 10.33369/joall.v5i1.9739
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies Employed by Efl Learners in a Rural Area

Abstract: Learning strategy has been widely acknowledged to play an important role in foreign language learning to help the learners in improving language competence. However, studies about language learning in EFL setting in various setting with different participants are still required as to provide a comprehensive representation of how language learning strategies are applied by L2 learners, particularly in an Indonesian EFL setting. This study aimed to examine what language learning strategies are used by EFL learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Last, Melvina, Lengkanawati, and Wirza (2020) who investigated secondary school students also confirmed the meta-cognitive strategies as the most frequently used by students. A slightly different result was represented in the study of language learning strategies used by the local tour guides at National Park of Bromo Tengger Semeru by Sakinah, Degeng, and Sahiruddin (2020). The result showed that the most frequent strategy used was compensation strategies.…”
Section: Language Learning Strategies: Contrasting English Department...mentioning
confidence: 94%
“…Last, Melvina, Lengkanawati, and Wirza (2020) who investigated secondary school students also confirmed the meta-cognitive strategies as the most frequently used by students. A slightly different result was represented in the study of language learning strategies used by the local tour guides at National Park of Bromo Tengger Semeru by Sakinah, Degeng, and Sahiruddin (2020). The result showed that the most frequent strategy used was compensation strategies.…”
Section: Language Learning Strategies: Contrasting English Department...mentioning
confidence: 94%